2018
DOI: 10.1101/450254
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Massively parallel fitness profiling reveals multiple novel enzymes inPseudomonas putidalysine metabolism

Abstract: 30Despite intensive study for 50 years, the biochemical and genetic links between lysine 31 metabolism and central metabolism in Pseudomonas putida remain unresolved. To establish 32 these biochemical links, we leveraged Random Barcode Transposon Sequencing (RB-TnSeq), a 33 genome-wide assay measuring the fitness of thousands of genes in parallel, to identify multiple 34 novel enzymes in both L-and D-lysine metabolism. We first describe three pathway enzymes 35 that catabolize L-2-aminoadipate (L-2AA) to 2-ket… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 64 publications
0
60
0
Order By: Relevance
“…While OplR-based biosensors may be able to aid in the selection of mutant acyl-coA ligases with enhanced activity, there remains a sizeable thermodynamic barrier for the cyclization of the 7-membered ring 1 Since naturally-occuring genetically encoded biosensors for chemicals of interest have the potential to be much more sensitive than those repurposed or evolved in the laboratory, it is critical to pursue rapid and efficient means of identifying them. The recent development of other high-throughput methods to associate genotypes with phenotypes, such as RB-TnSeq and CRISPRi, has created a large reservoir of data that can be easily mined for transcription factors useful in synthetic biology 22,[29][30][31] . Bacteria often locally regulate catabolism, thus allowing inference of genetic control by adjacent transcription factors once a catabolic pathway has been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…While OplR-based biosensors may be able to aid in the selection of mutant acyl-coA ligases with enhanced activity, there remains a sizeable thermodynamic barrier for the cyclization of the 7-membered ring 1 Since naturally-occuring genetically encoded biosensors for chemicals of interest have the potential to be much more sensitive than those repurposed or evolved in the laboratory, it is critical to pursue rapid and efficient means of identifying them. The recent development of other high-throughput methods to associate genotypes with phenotypes, such as RB-TnSeq and CRISPRi, has created a large reservoir of data that can be easily mined for transcription factors useful in synthetic biology 22,[29][30][31] . Bacteria often locally regulate catabolism, thus allowing inference of genetic control by adjacent transcription factors once a catabolic pathway has been discovered.…”
Section: Discussionmentioning
confidence: 99%
“…) involves the participation, in the first step, of a decarboxylase (LdcA) that generates cadaverine (Espinosa‐Urgel and Ramos, ; Revelles et al . , ; Idurthi et al ., ; Thompson et al ., ). In P. putida KT2440, cadaverine is then deaminated and cyclised to 1‐piperideine by a cadaverine aminotransferase (Revelles et al .…”
Section: Cadaverine Degradative Pathwaymentioning
confidence: 97%
“…One of the multiple pathways reported in Pseudomonas species for the degradation of L-lysine (Fig. 6) involves the participation, in the first step, of a decarboxylase (LdcA) that generates cadaverine (Espinosa-Urgel and Ramos, 2001;Revelles et al 2004Revelles et al , 2005Idurthi et al, 2016;Thompson et al, 2019a). In P. putida KT2440, cadaverine is then deaminated and cyclised to 1-piperideine by a cadaverine aminotransferase (Revelles et al 2005).…”
Section: Cadaverine Degradative Pathwaymentioning
confidence: 99%
“…Recently this utility has inspired much work to uncover missing steps in the lysine catabolism of P. putida. These missing steps included the discovery of an additional route of glutarate catabolism through a coA-independent route to succinate, in addition to the known coA-dependent route to acetyl-coA 14,16 (Figure 1). Recent work has also demonstrated that both glutarate catabolic pathways are highly upregulated in the presence of glutarate 16 .…”
Section: Introductionmentioning
confidence: 99%
“…These missing steps included the discovery of an additional route of glutarate catabolism through a coA-independent route to succinate, in addition to the known coA-dependent route to acetyl-coA 14,16 (Figure 1). Recent work has also demonstrated that both glutarate catabolic pathways are highly upregulated in the presence of glutarate 16 . While work in Pseudomonas aeruginosa has characterized a homolog of the regulator of the ketogenic pathway (GcdR) 17 , and work in Escherichia coli has preliminarily characterized the glucogenic pathway regulator (CsiR), no work has directly investigated the regulation of the P. putida L-lysine catabolic pathways.…”
Section: Introductionmentioning
confidence: 99%